The Role of Clinical Nutrition Specialists in Improving Dietary Adherence and Patient Outcomes among Individuals with Celiac Disease: Patients’ Perspectives from Al-Marj Medical Educational Center, Libya - Dr. Amna Mousa Mohamed; Dr. Rehab Faraj Belhamad; Dr Mona H. Alshlamani; Dr Samira Blkassem Othman (Journal of Scientific and Human Dimensions, 2026)
Celiac disease is a chronic autoimmune disorder requiring lifelong adherence to a gluten-free diet. Clinical nutrition specialists play a crucial role in supporting patients’ dietary adherence and improving health outcomes.Objective: This study aimed to evaluate the role of clinical nutrition specialists in improving dietary adherence and patient outcomes among individuals with celiac disease from patients’ perspectives at Al-Marj Medical Educational Center, Libya.Methods: A descriptive-analytical study was conducted on a random sample of 100 patients diagnosed with celiac disease. Data were collected using a structured questionnaire covering awareness, dietary behavior, nutritional counseling, and patient satisfaction. Data were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations.Results: The findings indicated a high level of patient awareness regarding the importance of a gluten-free diet. Participants reported a high level of satisfaction with clinical nutrition services, particularly in relation to nutritional counseling, individualized dietary planning, and continuous follow-up. Regular follow-up with clinical nutrition specialists was perceived to be associated with improved health outcomes and better dietary adherence. Economic, social, and psychological factors were identified as the main barriers to long-term adherence.Conclusion: Clinical nutrition specialists play a fundamental role in improving dietary adherence, patient education, and quality of life among individuals with celiac disease. Strengthening nutritional counseling services and addressing socioeconomic barriers are essential for optimal disease management.